Nanocarrier formulations with acaricide potential on Rhipicephalus (Boophilus) microplus. - FIGUEIREDO, A. (2018)
Rhipicephalus (Boophilus) microplus is a major source of economic losses on brazilian livestock, preventing further development of the sector. Parasitic resistance to commercial acaricide formulations, and the impact of their residues in Food-animal products are driving the search for new molecules and control methods.